(untitled) (Transport systems and technologies, 2019)
The article considers modern problems in deploying web-applications of transport enterprises on virtual or dedicated servers. The issues addressed in the article, in particular, include sudden failures that result in the suspension of web-resources and the inability to timely detect them. During these stops, developers will not immediately know what has happened, therefore, as a rule, the first to know that the web-application of transport enterprises is not working, learn users or managers. The article presents the solution to this problem by using modern web-technologies for monitoring web-content. The article deals with the development of an author’s web-content monitoring system, which will monitor the web-content at all times with a certain interval by requesting and verifying their web-based applications, and in the event that a web-site of transport enterprises sends an incorrect response, a notice will be made developers that the web-application does not work. The system is based on the Progressive Web App, which allows you to send messages to any user device and make it easy to use, as in browsers, or as a mobile application on your computer or smartphone. The client‟s part of the system is developed with the help of the framework Angular, which provides for increasing the efficiency of the system and displaying it on computers with large screens and small smartphones.